IL-22 Binding Protein (IL-22BP) in the Regulation of IL-22 Biology - Zenewicz, Lauren A. (Frontiers in Immunology, 2021)
Cytokines are powerful mediators of inflammation. Consequently, their potency is regulated in many ways to protect the host. Several cytokines, including IL-22, have coordinating binding proteins or soluble receptors that bind to the cytokine, block the interaction with the cellular receptor, and thus prevent cellular signaling. IL-22 is a critical cytokine in the modulation of tissue responses during inflammation and is highly upregulated in many chronic inflammatory disease patients, including those with psoriasis, rheumatoid arthritis, and inflammatory bowel disease (IBD). In healthy individuals, low levels of IL-22 are secreted by immune cells, mainly in the gastrointestinal (GI) tract. However, much of this IL-22 is likely not biologically active due to the high levels of IL-22 binding protein (IL-22BP) produced by intestinal dendritic cells (DCs). IL-22BP is a soluble receptor homolog that binds to IL-22 with greater affinity than the membrane spanning receptor. Much is known regarding the regulation and function of IL-22 in health and disease. However, less is known about IL-22BP. In this review, we will focus on IL-22BP, including its regulation, role in IL-22 biology and inflammation, and promise as a therapeutic. IL-22 can be protective or pathogenic, depending on the context of inflammation. IL-22BP also has divergent roles. Ongoing and forthcoming studies will expand our knowledge of IL-22BP and IL-22 biology, and suggest that IL-22BP holds promise as a way to regulate IL-22 biology in patients with chronic inflammatory disease.